Absolute ionization and dissociation cross sections of tetrahydrofuran: Fragmentation-ion production mechanisms - Wolff, W.; Rudek, B.; Silva, L. A. da [UNESP]; Hilgers, G.; Montenegro, E. C.; Homem, M. G. P. (Amer Inst Physics, 2019)
We report an experimental and theoretical investigation on the absolute ionization and fragmentation cross sections of tetrahydrofuran (THF, C4H8O), a base molecule of the DNA-backbone. The measurements enabled the identification of 50 ionic species produced by 12 eV up to 2000 eV electron impact which allowed us to make a close inspection of the mechanisms of both the primary vacancy production and the postcollisional fragmentation pathways which lead to the fragment ions. The experimental cross sections of the ionic species were examined in the framework of the fragmentation matrix model to attribute from which molecular orbitals (MOs) the electron is removed and find out the relative contribution of up to 15 outer and inner valence MOs in the fragment-ion production. A comparison between measured and calculated dissociative cross sections relative to the molecular parent ion cross section allowed us to clearly identify the prevalence of the single or double ionization in the fragment-ion production. Due to these different production mechanisms, the relative proportion of some ejected fragment-ions strongly depends on the impact energy. The single ionization of the MOs leading to selected fragment ions was compared to those measured at a low electron-impact energy using a reaction microscope with good agreement between the two techniques. The formation of the dications C4HnO2+, excluding the molecular parent dication, is also presented. Published under license by AIP Publishing.